1999
DOI: 10.1021/jp990161t
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of Pyrrole and Electrochemical Study of Polypyrrole. 2. Influence of Acidity on the Formation of Polypyrrole and the Multipathway Mechanism

Abstract: Potentiodynamic generation of polypyrrole films at an extremely low reaction rate causes the resulting material to show an additional oxidation wave that is more negative and sharper than the one normally observed. The additional peaklike oxidation wave belongs to an unknown structural entity PPy(II). The treatment of acetonitrile with basic alumina prevents its formation, whereas the addition of a low concentration of hydrochloric acid (10 -5 to 5 × 10 -5 M) to the acetonitrile electrolytic solution promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 84 publications
7
69
0
Order By: Relevance
“…Studies have shown that the rate of polymerization of pyrrole increases under acidic conditions. 43 TEM micrographs recorded of individual tubes show that the hollow cavity extends the entire length of the structure ( Figure 6a). It also confirmed that the tube morphology remained intact despite being removed from the surface and sonicated, indicating high structural stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Studies have shown that the rate of polymerization of pyrrole increases under acidic conditions. 43 TEM micrographs recorded of individual tubes show that the hollow cavity extends the entire length of the structure ( Figure 6a). It also confirmed that the tube morphology remained intact despite being removed from the surface and sonicated, indicating high structural stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H 2 deformation [35] (pointed by arrows in Fig. 6b, c), which would explain the low doping level as a consequence of partial chain saturation [29]. However, it is clear that under similar synthesis conditions degradation reactions are suppressed compared with Ppy/AA6082.…”
Section: Synthesis and Characterizationmentioning
confidence: 95%
“…490 cm -1 , indicate that the polymer chains consist principally of hydroxipyrrolidines and partially saturated pyrrolidines [27,28]. These functionalities, probably resulting from acid-catalyzed degradation reactions during Py electropolymerization in the aqueous synthesis medium [29][30][31], disrupt Ppy conjugation resulting in a less doped polymer. Similar reasoning cannot be applied to Ppy/AA5083 and Ppy/AA2024 that exhibit higher quality film structure (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Nevertheless, at a pH of 12.0, the currents obtained from the voltammograms were considerably lower and after cycle 5 there is evidence of a further drop in the current, Figure 8b, indicating poor stability in this highly alkaline solution. This is due to a loss in conductivity (29,30), to give more insulating polymer films and the decrease in current could arise from both the nature of the polymer film and the BSA (31,32). …”
Section: Ecs Transactionsmentioning
confidence: 99%